Analisa Hubungan antara Sanitasi Lingkungan dan Kegiatan Mencuci Tangan dengan Kejadian Diare di Wilayah Puskesmas Alak Kota Kupang - Muhammad Naufal Adinata; Theresia Adriana Enggelina Dorkas Willy; Mohammad Zainal Fatah (Media Gizi Kesmas, 2024)
Background: Diarrhea is a serious problem in many countries, especially in areas with poor sanitation. This is influenced by both the environment and individual behavior. Its impact is significant, especially on infants, children, and the elderly. In Indonesia, diarrhea remains an unresolved issue, especially in areas with limited access to clean water and adequate sanitation. Therefore, it is important to understand the factors related to sanitation and personal hygiene to prevent diarrhea. Objectives: Analyzing the relationship between environmental sanitation and good and correct hand washing behavior and the incidence of diarrhea in the work area of ​​the Alak Health Center, Kupang City. Methods: An analytic observational study with a cross-sectional approach was established. Data collection was obtained using questionnaire instruments, interviews and environmental observations. The sample consisted of 100 individuals residing in the Alak Sub-District, the working area of Alak Community Health Center, including the Nunhila, Nunbaundelha, Nunbaunsabu, Namosain, Alak, and Penkase-Oeleta neighborhoods, selected using the Slovin formula. Data were collected through a questionnaire and analyzed using the chi-square method. Results: The yields of this research shown that has relationship among the availability of clean water and the incidence of diarrhea (p-value 0.001), public waste disposal facilities (p value 0.000), and good hand washing behavior (p value 0.000). Conclusions: Availability of clean water, public waste disposal facilities, and good hand washing behavior are related to the incidence of diarrhea. The recommendations include paying attention to clean water supply, waste management, and promoting clean living behavior in the working area of ​​the Alak Health Center, Kupang City.